Oxygen Stoichiometry Effect on Polar Properties of LaAlO3/SrTiO3. (23rd April 2018) - Sharma, Pankaj; Huang, Zhen; Li, Mengsha; Li, Changjian; Hu, Songbai; Lee, Hyungwoo; Lee, Jung‐Woo; Eom, Chang‐Beom; Pennycook, Stephen J.; Seidel, Jan; Ariando,; Gruverman, Alexei
Abstract: Discovery of a ferroelectric‐like behavior of the LaAlO3 /SrTiO3 (LAO/STO) interfaces provides an attractive platform for the development of nanoelectronic devices with functionality that can be tuned by electrical or mechanical means. However, further progress in this direction critically depends on deeper understanding of the physicochemical mechanism of this phenomenon. In this report, this problem by testing the electronic properties of the LAO/STO heterostructures with oxygen stoichiometry used as a variable is addressed. Local probe measurements in conjunction with interface electrical characterization allow to establish the field‐driven reversible migration of oxygen vacancies as the origin of the ferroelectric‐like behavior in LAO/STO. In addition, it is shown that oxygen deficiency gives rise to the formation of micrometer‐long atomically sharp boundaries with robust piezoelectricity stemming from a significant strain gradient across the boundary region. These boundaries are not ferroelectric but they can modulate the local electronic characteristics at the interface. The obtained results open a possibility to design and engineer electromechanical functionality in a wide variety of nominally nonpolar and non‐piezoelectric complex oxide heterostructures and thin films. Abstract : Scanning probe microscopy images of LaAlO3 /SrTiO3 heterostructures with structural boundaries exhibiting polar behavior: (a) atomic force microscopy surface topography, (b) piezoresponse force microscopy (PFM), (c) electrostatic force microscopy, and (d) Kelvin probe microscopy. (e) PFM image of the electrically poled area with structural boundaries illustrating their robust nonswitchable piezoelectric response.